Renal Injuries in Primary Aldosteronism: Quantitative Histopathological Analysis of 19 Patients With Primary Adosteronism. Issue 2 (August 2021) - Ogata, Hiroko; Yamazaki, Yuto; Tezuka, Yuta; Gao, Xin; Omata, Kei; Ono, Yoshikiyo; Kawasaki, Yoshihide; Tanaka, Tomoaki; Nagano, Hidekazu; Wada, Norio; Oki, Yutaka; Ikeya, Akira; et al.
Abstract : The rapid progression of chronic kidney disease and higher incidence of cardiovascular complications are well known in patients with hyperaldosteronism. However, detailed renal histopathologic characteristics of this disease have remained unknown. Therefore, renal biopsy specimens of 19 cases with unilateral hyperaldosteronism were compared with 22 autopsy renal cases of estimated glomerular filtration rate-matched essential hypertension without nephropathy or endocrine disorders to explore the hyperaldosteronism-specific histopathologic renal changes in this study. Global and segmental glomerulosclerosis, interstitial fibrosis, infiltration of inflammatory cells, arteriosclerosis, hyalinization of arterioles and immunoreactivity of mineralocorticoid receptor, 11β-hydroxysteroid dehydrogenase type 1 and 2, and renin were all quantitatively evaluated. The ultrastructural analysis was added in 3 hyperaldosteronism cases. Both mineralocorticoid receptor ( P <0.01) and 11β-hydroxysteroid dehydrogenase type 2 ( P <0.01) were significantly higher in renal tubules of hyperaldosteronism, which could result in enhancement of in situ aldosterone effects in hyperaldosteronism kidneys. Interstitial fibrosis was significantly more marked in hyperaldosteronism ( P <0.01). The proportion of segmental glomerulosclerosis was also significantly higher in hyperaldosteronism ( P <0.01). There were no significant differences of global glomerulosclerosis between 2 groups ( P =0.08). Glomerular size was significantly larger in hyperaldosteronism ( P <0.01). In medium size artery, luminal stenosis tended to be more marked ( P =0.08), and intima-to-media ratio was significantly lower ( P =0.02) in hyperaldosteronism. Arteriolar hyalinization was significantly more pronounced ( P <0.01), especially at efferent arterioles ( P <0.01) in hyperaldosteronism. Results above demonstrated more pronounced whole renal damages in hyperaldosteronism. Results of our present study also indicated the potential clinical significance of early intervention using mineralocorticoid receptor antagonists or blockers. Abstract : Supplemental Digital Content is available in the text.